DEBT POLICY SUPPORTS GROWTH BUMN KARYA - Muhamad Sohibul Karib; Anita Roosmawarni; Marista Oktaviani (P3I UMSurabaya, 2024)
This research aims to determine the influence of Asset Tangibility, Net Profit Margin and Company Growth on the Debt Policy of BUMN Karya companies for the 2013-2022 period. This research is quantitative in nature with the data source used is secondary data. This research method uses multiple linear regression analysis with Saturated Sampling techniques . Data management uses the EViews 10 program tool with the best Fixed Effect Model (FEM) test results. The results of this research are that Tangibility Assets partially has a negative and insignificant effect, while Net Profit Margin partially has a significant negative effect. However, this is different from company growth, which partially has a significant positive effect on debt policy. Simultaneously, the results obtained show that Asset Tangibility, Net Profit Margin and Company Growth influence Debt Policy. The results of data processing show a coefficient of determination of 88.97%, which means the influence it has is quite significant.